Fertiliser marketing systems in India - Tandon, H. L. S.; Fertiliser Development and Consultation Organisation (New Delhi, India : Fertiliser Development and Consultation Organisation, 1992)
Contributed research papers.
Includes bibliographical references.
Keywords: Fertilizers -- India -- Marketing; Fertilizers -- Marketing